1996
DOI: 10.1074/jbc.271.31.18437
|View full text |Cite
|
Sign up to set email alerts
|

Functional Re-expression of Laminin-5 in Laminin-γ2-deficient Human Keratinocytes Modifies Cell Morphology, Motility, and Adhesion

Abstract: Herlitz junctional epidermolysis bullosa (H-JEB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 43 publications
1
51
0
1
Order By: Relevance
“…Indeed, hemidesmosomal structures are not observed in artificial epithelia reconstituted with H-JEB keratinocytes that either produce no laminin-5, or, like LSV5 cells, secrete scant amounts of this adhesion ligand. 17,20 In this system, the hemidesmosomes reconstitute in correspondence to the anchoring fibrils of the de-epidermized dermis. Therefore, as in normal skin, the laminin-5 deposited on the basement membrane induces formation of the anchoring filaments and mediates their connection with the collagen VII molecules on the basement membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, hemidesmosomal structures are not observed in artificial epithelia reconstituted with H-JEB keratinocytes that either produce no laminin-5, or, like LSV5 cells, secrete scant amounts of this adhesion ligand. 17,20 In this system, the hemidesmosomes reconstitute in correspondence to the anchoring fibrils of the de-epidermized dermis. Therefore, as in normal skin, the laminin-5 deposited on the basement membrane induces formation of the anchoring filaments and mediates their connection with the collagen VII molecules on the basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work, we described the re-expression of laminin-5 in the immortalized H-JEB keratinocytes LSV5-R infected with a retrovirus expressing a wild-type laminin ␥2 chain. 20 The transduced cells restructured focal adhesions, modified their morphology and motility, and improved their adhesion to the culture substrate, but failed to synthesize hemidesmosomal structures. These results contrasted with the observation that immortalized JEB keratinocytes deficient in the expression of integrin ␣6␤4 infected with retroviruses expressing the adequate wild-type transgene synthesize hemidesmosomal-like structures in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Prior approaches restored expression of a number of genes to epidermal cells in JEB and other skin diseases in vitro 24,25 and in regenerated tissue in vivo; 2,21-23 however, they relied on amphotropic retroviruses with all their attendant drawbacks. In the plasmid-based approach presented here, functional SB transposase is required for sustained corrective gene delivery because a nonfunctional mutant failed to maintain gene transfer, even in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that retroviral vector-mediated transduction of laminin-5 cDNA restores synthesis of functional laminin-5 and induces changes in focal adhesion and motility in Herlitz JEB keratinocytes (28). This study is the first step for an application of in vivo gene transfer for the treatment of the JEB genodermatosis.…”
Section: Fig 5 Sequence Of the 27-kbmentioning
confidence: 99%
“…NIH-3T3 fibroblasts (American Type Culture Collection, CRL 1658) were grown in Dulbecco's modified Eagle's medium supplemented with 10% bovine serum. Plasmid DNAs were purified using the silica columns from Qiagen (Hylden, Germany), and transfections were carried out in 24-well dishes using LipofectAMINE (Life Technologies, Inc.) as detailed elsewhere (28). Each DNA construct was tested in triplicate wells in three separate experiments.…”
Section: Methodsmentioning
confidence: 99%